NSP4 Gene Analysis of Rotaviruses Recovered from Infected Children with and without Diarrhea - Lee, Chun-Nan (American Society for Microbiology, 2000)
The transmembrane glycoprotein NSP4 functions as a viral enterotoxin capable of inducing diarrhea in young mice. It has been suggested that NSP4 may be a key determinant of rotavirus pathogenicity and a target for vaccine development. Twenty two G1P[6] rotaviruses from babies with and without diarrhea were comparatively analyzed along with reference strains and another 22 Taiwanese human rotaviruses of G and P combination types different from the G1P[6] type. The sequence variations in the NSP4 genes were studied by direct sequencing analysis of the amplicons of reverse transcription-PCR. Two genetic groups could be identified in this analysis. While the majority of these strains were closely related to the Wa strain, the G2 viruses were closely related to the S2 strain. Furthermore, phylogenetic analysis of the NSP4 gene among the G2 rotaviruses revealed three distinct lineages associated with DS-1, S2, and E210, respectively, as has been reported previously for the VP7 gene. However, we found no apparent correlation in the deduced amino acid sequences corresponding to the proposed enterotoxic peptide region between the rotaviruses recovered from individuals with and without diarrhea. The NSP4 gene product being a pathogenic determinant may not be a generalized phenomenon.